A COMPARISON BETWEEN GRAMMAR-TRANSLATION METHOD AND DIRECT METHOD IN IMPROBING PUPILâS VOCAB ULARY ACHIEVEMENT - Katemba, Caroline V.; Sormin, Elizabeth Riana (Journal of Language Pedagogy, 2011)
Nowadays, many language teachers use different kinds of teaching method. Applying a certain method is one of the important factors in language teaching, especially in teaching vocabulary. Vocabulary is one of the most important parts in learning a language. Therefore, teacher has to be more concern on the method for the effectiveness of the process itself. From the above reason, this study entitled